Proteasome inhibitor b-AP15 induces enhanced proteotoxicity by inhibiting cytoprotective aggresome formation. (28th April 2019) - Hillert, Ellin-Kristina; Brnjic, Slavica; Zhang, Xiaonan; Mazurkiewicz, Magdalena; Saei, Amir Ata; Mofers, Arjan; Selvaraju, Karthik; Zubarev, Roman; Linder, Stig; D'Arcy, Padraig
Abstract: Proteasome inhibitors have been shown to induce cell death in cancer cells by triggering an acute proteotoxic stress response characterized by accumulation of poly-ubiquitinated proteins, ER stress and the production of reactive oxygen species. The aggresome pathway has been described as an escape mechanism from proteotoxicity by sequestering toxic cellular aggregates. Here we show that b-AP15, a small-molecule inhibitor of proteasomal deubiquitinase activity, induces poly-ubiquitin accumulation in absence of aggresome formation. b-AP15 was found to affect organelle transport in treated cells, raising the possibility that microtubule-transport of toxic protein aggregates is inhibited, leading to enhanced cytotoxicity. In contrast to the antiproliferative effects of the clinically used proteasome inhibitor bortezomib, the effects of b-AP15 are not further enhanced by the histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA). Our results suggest an inhibitory effect of b-AP15 on the transport of misfolded proteins, resulting in a lack of aggresome formation, and a strong proteotoxic stress response. Highlights: The small-molecule UPS inhibitor b-AP15 prevents cytoprotective aggresome formation. b-AP15 has dominant negative effect over bortezomib. Strong cytotoxic effect induced by b-AP15 without adjuvant treatment with SAHA. Treatment with b-AP15 affects intracellular trafficking, enhancing its cytotoxicity. Results illustrate additional benefits of b-AP15 in cancer therapy.